Fatigue crack growth under remote and local compression – a state-of-the-art review - A. Chahardehi; A. Mehmanparast (Fracture and Structural Integrity)
There is an ever increasing need for accurate understanding of the fatigue crack growth behaviour in major engineering materials and components. With the move towards more complex, probabilistic assessments, the traditional ‘safe’ or conservative approach for prediction of fatigue crack growth rate may no longer be attractive. Current codes and standards tend to be ambiguous about the treatment of compressive stress cycles: on the one hand code guidance on fatigue crack initiation may be non-conservative, while assessment of crack propagation may be inconsistently conservative. Where codes are non-conservative they could lead to dangerous assessments. The current paper provides a critical review of state-of-the-art in literature and a study of current code implications.